Optimisation of Energy Consumption Balance in Multi-Hop Topology Wireless Sensor Networks for Environmental Monitoring Systems along Railway Tracks - Suharjono, Amin; Sadewa, Eskandaru Erin (Politeknik Negeri Semarang, 2025)
The implementation of IoT requires careful planning so that the system can function optimally. This study describes the planning of WSN development as a network in an IoT system with a long, straight topology, such as that found on railway tracks. The planning includes the use of appropriate technology with minimal power consumption. Three simulation scenarios were conducted using LPSAN, LPWAN, and a combination of both to compare their performance on a straight-line topology. The profile of each technology in LPSAN and LPWAN in terms of their performance in transmitting sensor data in the IoT system will be determined. The network lifetime performance is also determined to demonstrate the energy efficiency of each technology. Thus, the most optimal scenario in terms of configuration and topology in a straight-line network will be selected. From the experiments conducted, it is concluded that multihop topology is generally recommended for use in straight-line networks compared to star topology, except in conditions where nodes are very close to the gateway